2011
DOI: 10.1007/s11606-011-1740-7
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Quality of Care and the Sociodemographic Composition of Physicians’ Patient Panels: A Repeat Cross-Sectional Analysis

Abstract: BACKGROUND: Pay-for-performance programs could worsen health disparities if providers who care for disadvantaged patients face systematic barriers to providing high-quality care. Risk Medicare claims data and the association between quality and the sociodemographic composition of physicians' patient panels. KEY RESULTS: Across eight quality measures, physicians' quality of care was not consistently associated with the composition of their patient panel either in a single year or between time periods. For exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…1, 2 However, cancer screening in patients with limited life expectancy is unlikely to prevent death from cancer, and is quite likely to lead to unnecessary diagnoses and treatments in patients who otherwise would have died before the cancer became clinically apparent. 35 For example, randomized trials of mammography did not find a reduction in breast cancer mortality before seven years follow-up in women aged 65–75.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 However, cancer screening in patients with limited life expectancy is unlikely to prevent death from cancer, and is quite likely to lead to unnecessary diagnoses and treatments in patients who otherwise would have died before the cancer became clinically apparent. 35 For example, randomized trials of mammography did not find a reduction in breast cancer mortality before seven years follow-up in women aged 65–75.…”
Section: Introductionmentioning
confidence: 99%
“…We have also found evidence to suggest that PCP access and more severe symptomatology may partially explain the disproportionate ED use for ARS by patients with Medicaid and self‐pay insurance statuses, respectively . Other studies have shown patients' preferences for the ED for management of ACSCs to arise in some cases from the belief that their concerns will be taken more seriously, or that they will be treated more urgently or with greater ease of testing and management with medications . It is possible that patients appreciate differential treatment if they present to a PCP versus ED in terms of likelihood of receiving an antibiotic prescription.…”
Section: Introductionmentioning
confidence: 65%
“…5,6 Other studies have shown patients' preferences for the ED for management of ACSCs to arise in some cases from the belief that their concerns will be taken more seriously, or that they will be treated more urgently or with greater ease of testing and management with medications. 7 It is possible that patients appreciate differential treatment if they present to a PCP versus ED in terms of likelihood of receiving an antibiotic prescription. In this study, we seek to characterize and compare antibiotic prescribing behavior in the primary care setting and in EDs for uncomplicated ARS.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of prior studies in various clinical settings found close association between performance metrics and patient panel characteristics, and that not accounting for case mix could incorrectly identify outliers and mischaracterize practice variation. [37][38][39][40][41][42][43] Given the expanding role of interventions that aim to reduce variation through physician metrics, poorly reflective metrics may not only mislead efforts toward improving clinical practice and accountability but also exacerbate burnout. [44][45][46][47][48][49] Further investigations to determine how to best account for physician choice and case mix are needed, [50][51][52] but our results suggest that unadjusted LOS, in the absence of counterbalancing measures such as relative value units, is an unstable metric for comparing emergency physician performance with practice groups and that its use should be carefully reconsidered.…”
Section: Discussionmentioning
confidence: 99%